The Internalization of Moral Education Values among Adolescents through the Diba’ Al-Barzanji Tradition in the As-Sa’adah An-Nahdliyah Community - Via Hamida Lutfiatul Hasanah; Ehwanudin; Adi Wijaya (Bulletin of Pedagogical Research, 2025)
This study aims to describe the process of internalizing moral values among adolescents through the Diba’ Al-Barzanji tradition within the As-Sa’adah An-Nahdliyah Community in Nambah Dadi Village. The study is motivated by concerns regarding the decline of adolescent morality resulting from the influences of modernization and social media. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal that the Diba’ Al-Barzanji tradition functions as a form of non-formal religious education that instills moral values through three stages: value transformation, value transaction, and value transinternalization. The internalization process is carried out through religious advice, exemplary role modeling, habituation of worship practices, and adolescents’ emotional and spiritual experiences gained from reciting shalawat and listening to stories about the life of Prophet Muhammad (PBUH). The results indicate positive behavioral changes among adolescents, including improved politeness, discipline, responsibility, and a stronger commitment to Islamic teachings. This study highlights the significant role of local religious traditions in fostering adolescent moral development in the contemporary era.